Hypohydration adversely affects lactate threshold in endurance athletes - Kenefick, R. W.; Mahood, N. V.; Mattern, C. O.; Kertzer, R.; Quinn, T. J. (The Journal of Strength and Conditioning Research, 2002)
The purpose of this investigation was to observe the effect of hypohydration (4% body mass) on lactate threshold (LAT) in 14 collegiate athletes (8 men and 6 women; age, 20.9 ± 0.5 years; height, 171.1 ± 2.4 cm; weight, 64.8 ± 2.3 kg; O2max, 62.8 ± 1.9 ml·kg1·min1; percentage of fat, 11.4 ± 1.5%). Subjects performed 2 randomized, discontinuous treadmill bouts at a dry bulb temperature (Tdb) of 22° C to volitional exhaustion in 2 states of hydration, euhydrated and hypohydrated. The hypohydrated condition was achieved in a thermally neutral environment (Tdb, 22° C; humidity, 45%), with exercise conducted at a moderate intensity as defined by rating of perceived exertion (RPE, approximately 12) 12-16 hours before testing. On average, subjects decreased 3.9% of their body mass before the hypohydration test. Blood lactate, hematocrit, O2, minute ventilation (E), R value, heart rate (HR), and RPE were measured during each 4-minute stage of testing. In the hypohydrated condition, LAT occurred significantly earlier during exercise and at a lower absolute O2, E, respiratory exchange ratio, RPE, and blood lactate concentration. Also, the blood lactate concentration was significantly lower in the hypohydrated condition (6.7 ± 0.8 mmol) compared with the euhydrated condition (10.2 ± 0.9 mmol) at peak exercise. There were no differences in HR or percentage of maximum HR at LAT nor did plots of CO2:O2 reveal differences in bicarbonate buffering during exercise between the 2 conditions. From these results, we speculate that hypohydration did not significantly alter cardiovascular function or buffering capacity but did cause LAT to occur at a lower absolute exercise intensity.